Defense policy shaping foreign policy : an alternative interpretation through the study of the Argentine-Chilean relations - Magnani, Ezequiel (2022)
Fil: Magnani, Ezequiel. Universidad Torcuato Di Tella. Departamento de Ciencia Política y Estudios Internacionales; Argentina